Mammalian adaptation risk in HPAI H5N8: a comprehensive model bridging experimental data with mathematical insights - Santosh Chokkakula; Sol Oh; Won-Suk Choi; Chang Il Kim; Ju Hwan Jeong; Beom Kyu Kim; Ji-Hyun Park; Seong Cheol Min; Eung-Gook Kim; Yun Hee Baek; Young Ki Choi; Min-Suk Song (Emerging Microbes and Infections)
Understanding the mammalian pathogenesis and interspecies transmission of HPAI H5N8 virus hinges on mapping its adaptive markers. We used deep sequencing to track these markers over five passages in murine lung tissue. Subsequently, we evaluated the growth, selection, and RNA load of eight recombinant viruses with mammalian adaptive markers. By leveraging an integrated non-linear regression model, we quantitatively determined the influence of these markers on growth, adaptation, and RNA expression in mammalian hosts. Furthermore, our findings revealed that the interplay of these markers can lead to synergistic, additive, or antagonistic effects when combined. The elucidation distance method then transformed these results into distinct values, facilitating the derivation of a risk score for each marker. In vivo tests affirmed the accuracy of scores. As more mutations were incorporated, the overall risk score of virus heightened, and the optimal interplay between markers became essential for risk augmentation. Our study provides a robust model to assess risk from adaptive markers of HPAI H5N8, guiding strategies against future influenza threats.